Health Status, Family Support, and Independence in Activities of Daily Living among Adults Aged 45 Years and Older at Posbindu Tabeo, Central Sulawesi - Rina Tampake; Jurana Jurana; Dwi Yulia Vasya; Rahmat Kurniawan; Selvi Alfrida Mangundap (Salando Health Journal, 2026)
Background: Independence in performing activities of daily living (ADL) is an important indicator of functional health among middle-aged and older adults. Health status and family support are considered important factors associated with the ability to maintain daily functioning. This study aimed to analyze the association between health status, family support, and independence in ADL among adults aged 45 years and older at Posbindu Tabeo, Kayumalue Ngapa, within the working area of Tawaeli Public Health Center, Central Sulawesi, Indonesia. Methods: This study employed an analytical cross-sectional design. The study was conducted at Posbindu Tabeo, Kayumalue Ngapa, from July 10 to July 11, 2023. A total of 38 participants aged 45 years and older were selected using purposive sampling. Data were collected through face-to-face interviews using structured questionnaires. Independence in ADL was measured using the Barthel Index, while health status and family support were assessed using structured questionnaires. Data were analyzed using descriptive statistics and the Chi-square test, with statistical significance set at p < 0.05. Results: Among 38 participants, 28 respondents (73.7%) had good health status, 27 respondents (71.1%) received supportive family support, and 17 respondents (44.7%) had mild dependency in ADL. The Chi-square test showed a significant association between health status and independence in ADL (p = 0.001). A significant association was also found between family support and independence in ADL (p = 0.001). Conclusion: Health status and family support were statistically associated with independence in activities of daily living among adults aged 45 years and older at Posbindu Tabeo. These findings suggest the importance of maintaining good health status and strengthening family support in community-based health programs to help preserve functional independence. Further studies with larger samples and longitudinal designs are recommended to confirm these findings.